Alexander Pope: Unlocking the key - Johnston, F (Oxford University Press, 2016)
This article discusses the image and function of the key in Alexander Pope’s works, and its involvement in various attempts to understand and explain him. As a device for encrypting or decrypting a code, a ‘key’ permits either the further concealment or revelation of meaning, and sometimes both: a sense which enters the language with Francis Bacon in 1605, but which is not fully realized as a satirical opportunity until the early eighteenth century. The subgenre of the ‘key’ may be a small part of the unwholesome trade of deciphering, but it raises vital questions about originality, authority, cooperation, competition, and group identity. Keys to Pope’s, Swift’s, and Gay’s works suggest some fruitful ways in which to track rival theories about their own writing and its reception; at its ornate Scriblerian best, the key is a riddling device, furthering the obscurity rather than breaching the mysterious specificity of the original.